Local tumour control and eye preservation after gamma-knife radiosurgery of choroidal melanomas. Issue 2 (29th October 2013) - Wackernagel, Werner; Holl, Etienne; Tarmann, Lisa; Mayer, Christoph; Avian, Alexander; Schneider, Mona; Kapp, Karin S; Langmann, Gerald
Abstract : Background/aims: To report on local tumour control and eye preservation after gamma knife radiosurgery (GK-RS) to treat choroidal melanomas. Methods: A total of 189 patients with choroidal melanoma were treated with GK-RS, with treatment doses between 25 and 80 Grays. The main outcome measures of our retrospective analysis were local tumour control, time to recurrence, eye retention rate and the reason for and time to secondary enucleation. Patient-associated, tumour-associated and treatment-associated parameters were evaluated as potential risk factors. Results: Local tumour control was achieved in 94.4% of patients. The estimated tumour control rates were 97.6% at 1 year, 94.2% at 5 years and 92.4% at 10 years after treatment. Recurrence was observed between 3.1 months and 60.7 months post-treatment (median: 13.5 months). Advanced tumour stage (Tumour, Node, Metastasis (TNM) 3–4) was the most important risk factor for recurrence (Fine-Gray model; subhazard ratio, SHR: 3.3; p=0.079). The treatment dose was not related to tumour recurrence. The eye preservation rate was 81.6% at 5 years after treatment, remaining stable thereafter. Twenty-five eyes (14.1%) had to be enucleated at between 17 days and 68.0 months (median: 13.9 months) after GK-RS, and advanced tumour stage (Cox model; p=0.005), treatment dose (p=0.048), pretreatment visual acuity (p=0.016), and retinal detachment (p=0.027) were risk factors for requiring enucleation. Conclusions: GK-RS achieved a high tumour control rate, comparable to linear accelerator-based radiotherapy. Advanced TNM stage was a predictive risk factor for tumour recurrence and for secondary enucleation after GK-RS. Lower treatment doses were unrelated to tumour recurrence, although they were associated with an improved eye retention rate.